2017
DOI: 10.1002/pon.4513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fatigue, depression, and anxiety as factors affecting posttreatment health‐related quality of life in lung cancer survivors

Abstract: Relative to depression and anxiety, fatigue exerted a stronger effect on lung cancer survivors' HRQoL. Health professionals should consider the reduction of fatigue a priority in improving cancer patients' HRQoL following the completion of cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 33 publications
4
32
0
2
Order By: Relevance
“…Besides CIPN, fatigue is also a highly prevalent problem among cancer survivors, with prevalence rates up to 90% . Fatigue is one of the most debilitating symptom among cancer patients and has been related to a worse HRQoL, a higher cancer recurrence, and a poorer survival . CIPN has been related to fatigue in previous research, but the mechanisms underlying this relationship are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides CIPN, fatigue is also a highly prevalent problem among cancer survivors, with prevalence rates up to 90% . Fatigue is one of the most debilitating symptom among cancer patients and has been related to a worse HRQoL, a higher cancer recurrence, and a poorer survival . CIPN has been related to fatigue in previous research, but the mechanisms underlying this relationship are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is described as being subjective, multidimensional and variable in severity with physical, emotional, mental, functional and spiritual components (Pearson, Morris, Stefano, & McKinstry, ; Wu & Davis, ). Studies exploring patients' symptom experiences have shown that patients consistently rate fatigue as the most severe symptom, compromising the individual's physical functioning as well as their quality of life (Jung et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ha and colleagues report borderline anxiety and depression scores (> seven on the HADS subscales) in 19% and 31% of participants respectively. Recent work in a sample of 830 lung cancer survivors reports similar rates of borderline anxiety (21%) and higher rates of borderline depression (39%) (24). Abnormal levels of fatigue (scores >40) were also reported in 42% of participants in the study by Jung and colleagues (24), compared to only 24% reported by Ha and colleagues.…”
mentioning
confidence: 86%
“…Recent work in a sample of 830 lung cancer survivors reports similar rates of borderline anxiety (21%) and higher rates of borderline depression (39%) (24). Abnormal levels of fatigue (scores >40) were also reported in 42% of participants in the study by Jung and colleagues (24), compared to only 24% reported by Ha and colleagues. Hospitalised patients prior to commencing treatment report high levels of anxiety and depression (65% for both anxiety and depression) (25).…”
mentioning
confidence: 86%